Analyzing broadband networks - Mark A Miller (M.T books, 1994)
Broadband technologies; Frame relay architecture; Frame relay protocols; Frame relay analysis; SMDS architecture; Protocol; Analysis; ATM architecture; Protocols; Analysis; Managing broadband networks.